2016
DOI: 10.1016/j.vetpar.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo action of Piptadenia viridiflora (Kunth) Benth against Haemonchus contortus in sheep

Abstract: Anthelminthic resistant populations of Haemonchus contortus are a major problem in sheep rearing, but plant extracts may offer viable alternative treatments. In our preliminary studies, Piptadenia viridiflora was frequently selected by sheep grazing in the Cerrado. The present research evaluated its in vitro and in vivo anthelmintic activity. The HPLC chromatograms of P. viridiflora aqueous extract (AE) and ethanolic extract (EE) showed the presence of flavonoids. The total condensed tannin (proanthocyanidin) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 30 publications
3
26
0
Order By: Relevance
“…Other studies reported a 90% to 100% reduction of infecting larvae in vitro; however, the RFEC was 53% (Nery et al, 2012), 47.20% (Morais Costa et al, 2016, and 33% (Nogueira et al, 2012). All alcoholic extracts evaluated in vitro showed promising effects (Assis et al, 2003;Almeida et al, 2004;Cordeiro et al, 2010;Gomes et al, 2010;Nery et al, 2010;Araújo et al, 2011;Tenório et al, 2015a;Morais Costa et al, 2016). Under in vivo condition, just alcoholic extract of O. hamiltonii showed satisfactory results (Brito-Júnior et al, 2011).…”
Section: Forms Of Plants For Use As Anthelminticsmentioning
confidence: 96%
See 2 more Smart Citations
“…Other studies reported a 90% to 100% reduction of infecting larvae in vitro; however, the RFEC was 53% (Nery et al, 2012), 47.20% (Morais Costa et al, 2016, and 33% (Nogueira et al, 2012). All alcoholic extracts evaluated in vitro showed promising effects (Assis et al, 2003;Almeida et al, 2004;Cordeiro et al, 2010;Gomes et al, 2010;Nery et al, 2010;Araújo et al, 2011;Tenório et al, 2015a;Morais Costa et al, 2016). Under in vivo condition, just alcoholic extract of O. hamiltonii showed satisfactory results (Brito-Júnior et al, 2011).…”
Section: Forms Of Plants For Use As Anthelminticsmentioning
confidence: 96%
“…Although the extractive preparation methodology is relatively standardized, the substances used in the extraction process directly influences the extract yield and content of the final product (Xynos et al, 2012;Oliveira et al, 2016). Egg hatchability and/or larval development was reduced by more than 80% in 88,88% aqueous extracts under in vitro conditions for at least one of the concentrations used (Nery et al, 2010;Oliveira et al, 2010;Ferreira et al, 2013;Salas et al, 2013;Cunha et al, 2014;Morais Costa et al, 2016). No aqueous extracts showed an RFEC (reduction faecal egg count) greater than 80% under in vivo conditions; however, 71.42% of the extracts had RFEC of 50-80% Botura et al, 2011;Domingues et al, 2013;Pereira et al, 2013;Silva et al, 2013;Mendonça-Lima et al, 2016;Coêlho et al, 2017).…”
Section: Forms Of Plants For Use As Anthelminticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, mean FEC was calculated on days 7, 8, and 9 (second period); days 14, 15, and 16 (third period). Each period covered an average of 3 days, obtaining two counts each day (Morais-Costa et al, 2016).…”
Section: In Vivo Test In Lambsmentioning
confidence: 99%
“…Blood samples were collected from the jugular vein into tubes containing ethylene diamine tetra-acetic acid (EDTA) and stored at 4 °C (Morais-Costa et al, 2016). The blood cell numbers and hematocrit were evaluated in an electronic automatic analyzer (2.800 BC Vet ® , Mindray Medical International Ltd. Shenzhen, China).…”
Section: Blood Parametersmentioning
confidence: 99%